Complexing of chlorogenic acid with β-cyclodextrins: Inclusion effects, antioxidative properties and potential application in grape juice - Shao, P.; Zhang, J.; Fang, Zhongxiang; Sun, P. (Elsevier BV, 2014)
Chlorogenic acid (CGA) is a polyphenol commonly existed in fruits and vegetables with a variety of bioactivities. To increase its stability and potential broader industrial application, CGA/cyclodextrin (CD) complexes were prepared using β-cyclodextrin (β-CD) and its derivative (2-hydroxypropyl)-β-cyclodextrin (2-HP-β-CD). Their inclusion complexation behavior and characterization were investigated by FT-IR, XRD, SEM, and 1H NMR spectroscopy. The morphologic and spectral studies indicated the formation of inclusion complexes. Moreover, spatial arrangements of inclusion complexes were proposed based on 1H NMR results. The antioxidant activities of the complexes were improved compared with the CGA without inclusion, and the CGA/HP-β-CD complexes showed the highest antioxidant activity. In addition, the CGA/CD complexes were added in grape juice to explore the potential on the preservation of anthocyanin and color quality. Results showed that the degradation of anthocyanins was reduced when CGA and CGA/CDs inclusions were added in grape juice due to copigmentation effect, and their copigmentation strength showed in an order of CGA/HP-β-CD complex > CGA/β-CD complex > free CGA.